Menguji Virtual Reality dengan Metode Pembelajaran Konvensional di Kalangan Gen - Z atau Alfa : [Testing Virtual Reality with Conventional Learning Methods Among Gen - Z or Alpha] - Ade Eva Novianti (Jurnal Teropong Pendidikan, 2024)
This study highlights the need for the education system to adapt to the rapid development of technology, especially in response to changes in student behavior, particularly those from Generation Z and Alpha. The researcher suggests that effective learning methods can no longer rely solely on a single approach, such as the traditional verbal method, but must integrate other methods, particularly the use of technology like virtual reality (VR), to create more engaging and effective learning experiences. Based on the results of this study, which used a qualitative approach with virtual reality as the research instrument, 80% of respondents found learning with VR to be enjoyable, while only 3 out of 15 respondents showed interest in conventional methods. These findings indicate that the use of technology, especially VR, has great potential to meet the preferences of younger generations, who are more accustomed to technology and require a more interactive and innovative approach to learning. This research provides valuable insights for educators to consider incorporating technology into the learning process, as a way to address the behavioral changes and needs of Generation Z and Alpha, who are more dynamic. By leveraging technology, educators can create a more enjoyable and effective learning environment, ultimately improving students' learning outcomes.